An analysis of clinical trials registered with CTRI in India from 2007 to 2015 - Chawan, Vihang S.; Badwane, Sagar V.; Gawand, Kalpesh V.; Chhaya, Maheshi U. (International Journal of Clinical Trials, 2016)
Background: Clinical trials are gold standard in the field of evidence based medicine. Registration of clinical trials facilitates the dissemination of information among clinicians, researchers and patients. Earlier, researchers were interested only in publishing positive results of their study. The negative results were never published resulting in bias in reporting the results of such clinical trials. It is now mandatory to register all clinical trials done in India at National Institute of Medical Statistics (NIMS) hosted at Clinical Trial Registry - India (CTRI) website to ensure transparency, accountability and accessibility of clinical trials. This study was planned to analyze the number of clinical trials registered under CTRI from 2007 to 2015. The information regarding the registration of clinical trials was accessed from the website www.ctri.nic.in. Methods: The information on registered clinical trials was obtained from the website www.ctri.nic.in. The clinical trials registered with CTRI from 2007 to 2015 were noted for analysis. Results: Maximum number of clinical trials registered in the year 2015 (1113), followed by year 2014 (1089), 2013 (990), 2012 (959) and 2011 (748) while least number of clinical trials registered in the year 2007 (32). Results revealed that there is wide gap the number of clinical trials registered in between year 2007 to 2015 and also revealed that number of clinical trials registered are increasing in order from year 2007 to year 2015. Conclusions: The registrations of clinical trials improve the reliability of data generated, assist clinicians to interpret research, minimizes duplication of trials and prevents exposure of volunteers to potential risks.